Marriage and family in view of the doctrine of the covenant - Vorster, J. M. (HTS teologiese studies, 2016)
New emerging paradigms in Western culture have produced a new ethic. Not only social ethics in general but the ethics of marriage and family life are changing rapidly. This new ethic has inter alia a strong bearing on marriage and family life, relationships explained by traditional Christian ethics. The traditional idea of heterosexual official marriages is challenged by new forms of civil relationships such as cohabitation, temporary relationships and civil unions between gay couples. Scholars even speak of the postmodernist marriage that, according to them, differs entirely from the traditional Christian idea of marriage. This article focuses on the concepts of marriage and family life against the background of the emerging postmodern and post-secular ethic and its consequences for the traditional view of marriage as a biblical institution. The central theoretical argument is that the concept of marriage in the biblical testimony should be defined and developed within the doctrine of the covenant and that such as view, with certain modifications, can still provide ethical directives and new perspectives on marital life for Christians today.Keywords: Marriage; Covenant; Post Modernism: Secular; Family